Analysis of Lead Metal Contents (Pb) in Various Cosmetic Dosage Forms Using the Atomic Absorption Spectrophotometry (AAS) Method - Permatasari, Amelia Dyah; Syifa, Dewi Musnifatus; Zabrina, Leilani; Artanti, Naura; Sari, Novia; Desnita, Syifa (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2024)
Cosmetics are the preparations whose products are most widely used by people in all circles, from babies to adults. However, it is not uncommon to find dangerous substances contained in cosmetics, one of which is lead contamination, so it is necessary to test the dangerous substances in them. This review aims to provide information regarding the presence and levels of the heavy metal lead in various cosmetic samples using the atomic absorption spectrophotometry method and to analyze the dangers it causes. The method used is a literature review of articles with the keywords "cosmetics", "heavy metals", "lead pollution", "health risks" and "atomic absorption spectrophotometer" between 2019-2023. The results of the review that has been carried out are that the majority of cosmetics contain the heavy metal lead (Pb), either within the required limits or exceeding the required limits. The dangers posed by lead contamination in cosmetics used over a long period of time can be similar to acute or chronic toxic diseases, and can result in pathological changes in body organs such as the cardiovascular system, kidneys, bones, liver, potentially causing cancer and genetic changes. and the most fatal form of lead poisoning can cause death